PENGARUH CORPORATE GOVERNANCE, SISTEM WHISTLEBLOWING, DAN PENGENDALIAN INTERNAL TERHADAP PENGUNGKAPAN KECURANGAN DI PERUSAHAAN KOTA BATAM - angelina Angelina; Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2026)
This study examines the influence of corporate governance, whistleblowing systems, and internal control on fraud disclosure in companies located in Batam City. The research addresses the persistent issue of fraud in organizational settings and aims to analyze how governance mechanisms and control systems contribute to fraud disclosure practices. A quantitative research design was employed, using primary data collected through questionnaires distributed to 100 employees selected via purposive sampling. The data were analyzed using descriptive statistical analysis and multiple linear regression techniques. The results indicate that whistleblowing systems and internal control have a positive and significant effect on fraud disclosure, whereas corporate governance does not exhibit a significant individual effect. However, the simultaneous test demonstrates that corporate governance, whistleblowing systems, and internal control collectively have a significant influence on fraud disclosure. These findings highlight the importance of strengthening internal control mechanisms and establishing effective whistleblowing systems to enhance transparency and reduce the risk of fraud within companies.